2013
DOI: 10.1016/j.nrl.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la función ejecutiva en una población escolar con síntomas de déficit de atención e hiperactividad

Abstract: EF measures in children with ADHD revealed more problems, particularly those having to do within planning, inhibition, working memory and cognitive control. Age and sex may affect the degree of EF impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
3
3
0
14
Order By: Relevance
“…This finding is consistent with those of Borkowska et al (2011) and Vélez- Van-Meerbeke et al (2013). In contrast, Mesquita et al (2010) did not find significant differences between the ADHD and control groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with those of Borkowska et al (2011) and Vélez- Van-Meerbeke et al (2013). In contrast, Mesquita et al (2010) did not find significant differences between the ADHD and control groups.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those reported by Brunswick et al (2010), Cruz-Rodrigues et al (2014), andMcManus et al (2010). There were no significant differences between the groups with dyslexia and ADHD either, but some studies have reported changes in immediate memory recall in students with these disorders (Borkowska et al, 2011;Duranovic et al, 2015;Vélez-Van-Meerbeke et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…[3][4][5] Perturbações no funcionamento executivo traduzem-se em menor capacidade de resolução de problemas complexos, menos competências organizativas e estratégias de memória deficientes em crianças com PHDA. 6 O funcionamento executivo é um constructo complexo e de difícil definição.…”
Section: 2unclassified
“…Son numerosos los estudios que evidencian que los niños con TDAH presentan un déficit en las FE, como la inhibición del comportamiento (Alloway, 2011;Barkley, 2011;Martel, Nikolas, & Nigg, 2007;Rubiales, Bakker, & Urquijo, 2010;Schoemaker et al, 2012), la flexibilidad cognitiva (Martel et al, 2007;Vélez-van-Meerbeke et al, 2013;Ferreiro-Vilasante, Buceta-Cancela, & Rial-Boubeta, 2013) y la planificación y organización (RamosLoyo, Taracena, Sánchez-Loyo, Matute, & González-Garrido, 2011;Semrud-Clikeman, Walkowiak, Wilkinson, & Butcher, 2010). Dicha disfunción ejecutiva se manifiesta a través de un bajo rendimiento en las tareas que evalúan las funciones anteriormente mencionadas, siendo el TDAH un trastorno heterogéneo y complejo, que tiene una gran variabilidad en la manifestación de sus síntomas, los cuales pueden conllevar a dificultades en el ámbito escolar, familiar y social del niño (Chhabildas, Pennington, & Willcutt, 2001).…”
Section: Introductionunclassified